Willingness to communicate in digital and non-digital EFL contexts: scale development and psychometric testing. Issue 7 (2nd September 2020) - Lee, Ju Seong; Drajati, Nur Arifah
Abstract: This study introduces a new scale of willingness to communicate in a second language (L2 WTC) in digital and non-digital EFL contexts. The psychometric testing of the revised L2 WTC (L2 WTC-R) was undertaken with 114 Indonesian EFL students by means of exploratory factor analysis (EFA). The results yielded an 11-item scale composed of three factors ( L2 WTC inside the classroom, L2 WTC outside the classroom, and L2 WTC in the context of informal digital learning of English [IDLE] ), with strong reliability and validity evidences. Confirmatory Factor Analysis was subsequently administered for a new sample (215 Indonesian EFL students), confirming the three-factor model that emerged from EFA. These results not only validate the existing L2 WTC scale but also expand its scale into digital settings, which will enable future research to consider another domain of L2 WTC (the IDLE context). From a real-world perspective, this can serve as a useful instrument for practitioners to gauge and foster L2 WTC levels in digital and non-digital contexts.